Development and Evaluation of the Perpetration‐Induced Distress Scale for Measuring Shame and Guilt in Civilian Populations. Issue 3 (20th March 2019) - Steinmetz, Sarah E.; Gray, Matt J.; Clapp, Joshua D.
Abstract: Although the topic of moral injury (MI) has been garnering increasing attention in recent years within military populations, research has rarely applied the concept to civilian contexts. Extant literature on distinct acts of perpetration or transgressions suggests similar emotional, cognitive, and behavioral patterns of distress associated with appraisals of wrongdoing. However, the absence of a psychometrically sound measure to detect and quantify pathological levels of distress associated with perpetrating harm against others has hindered additional research from being conducted on the topic. The current research presents the Perpetration‐Induced Distress Scale (PIDS) as a valid and reliable measurement of distress associated with MI within civilian contexts. Factor analytic techniques revealed a two‐factor solution characterized by perpetration‐induced distress related to maladaptive reactions to shame (seven items) and guilt/self‐blame (seven items). The PIDS demonstrated favorable temporal stability over a 1‐week period as well as excellent internal reliability. Further, the PIDS evidenced convergent validity with functional impairment, posttraumatic stress disorder, and existing scales of shame and guilt; associations were large (rs = 0.62–0.87). The development of the PIDS represents one of the first studies to measure MI within a civilian population and indicates evidence that additional research on the topic is warranted. Resumen: Spanish Abstracts by Asociación Chilena de Estrés Traumático (ACET) Desarrollo y evaluación de la escala de malestar psicológico inducida por la perpetración para medir la vergüenza y la culpa en poblaciones civiles MALESTAR INDUCIDO POR PERPETRACION EN CIVILES Aunque el tema del daño moral (DM) ha estado recibiendo una atención creciente en los últimos años dentro de las poblaciones militares, la investigación rara vez ha aplicado este concepto a contextos civiles. La literatura existente sobre distintos actos de perpetración o transgresiones sugieren patrones similares de malestar psicológico emocional, cognitivo y conductual asociados con evaluaciones de irregularidades. Sin embargo, la ausencia de una medida psicométricamente sólida para detectar y cuantificar los niveles patológicos de malestar psicológico asociados con la perpetración de daños contra otros ha obstaculizado la realización de investigaciones adicionales sobre el tema. La investigación actual presenta la Escala de Malestar Psicológico inducida por perpetración (PIDS en su sigla en inglés) como una medida válida y confiable del malestar psicológico asociada con DM dentro de contextos civiles. Las técnicas analíticas de factores revelaron una solución de dos factores caracterizada por el malestar psicológico inducido por perpetración relacionada con reacciones desadaptativas a la vergüenza (siete elementos) y culpa / autoculpa (siete elementos). El PIDS demostró una estabilidad temporal favorable durante un período de 1 semana, así como una excelente fiabilidad interna. Además, el PIDS evidenció validez convergente con deterioro funcional, trastorno de estrés postraumático y escalas existentes de vergüenza y culpa, con asociaciones grandes. El desarrollo del PIDS representa uno de los primeros estudios en medir el DM dentro de una población civil e muestra evidencia de que la investigación adicional sobre el tema es justificada. 抽象: Traditional and Simplified Chinese Abstracts by the Asian Society for Traumatic Stress Studies (AsianSTSS) 簡體及繁體中文撮要由亞洲創傷心理研究學會翻譯 Development and Evaluation of the Perpetration‐Induced Distress Scale for Measuring Shame and Guilt in Civilian Populations Traditional Chinese 標題: 用以測量平民百姓的羞恥和內疚的「犯罪引致的悲痛量表」的發展和檢討 撮要: 近年，道德創傷(MI)在軍事人口裡取得越來越高的關注。可是，仍少有研究檢視平民百姓的MI。過往有關明顯的犯罪或犯法行為的文獻，指出與錯事的評價相關的悲痛有相似的情感、認知和行為模式。然而，有關與對他人構成傷害的犯罪相關的悲痛水平，我們缺乏有效的心理測量工具去檢測和量化，以致這方面的研究停滯不前。本研究將顯示「犯罪引致的悲痛量表(PIDS)」對平民百姓與MI有關的悲痛，屬有效和可靠的測量工具。因素分析技術反映出二因解決方案:與對羞恥（七項）的適應不良反應有關、因犯罪引致的悲痛;與對內疚/自責（七項）的適應不良反應有關、因犯罪引致的悲痛。在為期一星期的時間裡，PIDS展現良好的時間穩定性，亦有優良的內在可靠性。此外，PIDS在功能受損、創傷後壓力症、及既有的羞恥和內疚量表方面，都有良好的聚合效度，當中的關連強勁。PIDS的發展屬檢測平民百姓MI的首批研究，並反映未來有需要在這方面作更多研究。 Simplified Chinese 标题: 用以测量平民百姓的羞耻和内疚的「犯罪引致的悲痛量表」的发展和检讨 撮要: 近年，道德创伤(MI)在军事人口里取得越来越高的关注。可是，仍少有研究检视平民百姓的MI。过往有关明显的犯罪或犯法行为的文献，指出与错事的评价相关的悲痛有相似的情感、认知和行为模式。然而，有关与对他人构成伤害的犯罪相关的悲痛水平，我们缺乏有效的心理测量工具去检测和量化，以致这方面的研究停滞不前。本研究将显示「犯罪引致的悲痛量表(PIDS)」对平民百姓与MI有关的悲痛，属有效和可靠的测量工具。因素分析技术反映出二因解决方案:与对羞耻（七项）的适应不良反应有关、因犯罪引致的悲痛;与对内疚/自责（七项）的适应不良反应有关、因犯罪引致的悲痛。在为期一星期的时间里，PIDS展现良好的时间稳定性，亦有优良的内在可靠性。此外，PIDS在功能受损、创伤后压力症、及既有的羞耻和内疚量表方面，都有良好的聚合效度，当中的关连强劲。PIDS的发展属检测平民百姓MI的首批研究，并反映未来有需要在这方面作更多研究。